Denouncing cultural stereotypes against black women in the contemporary South African society through the prism of Northern Sotho cultural proverbs - Montle, Malesela Edward (Penerbit Universiti Kebangsaan Malaysia, 2021)
The fundamental assumptions of women in African societies were and are still underpinned by stereotypical notions. Specifically, it is the cultural stereotypes, inter alia, that assert gratuitous societal roles that often marginalise women. Today, (South) Africa is vexed by upsurging issues such as femicide, sexism and domestic violence as a result of the cultural stereotypes that, particularly, perturb black women. Therefore, to explore these cultural notions that pose a menace to black women’s lives, this qualitative study sought to denounce some of the cultural stereotypes that perpetuate socio-economic and political maladies against black (South) African women. It is undergirded by the theoretical framework of cultural identity and feminism which serve as grounding for the study. The latter has drawn mainly from purposively selected Northern Sotho cultural proverbs coupled with supplementary data collected from critical essays, journal articles and books. The study, among other discoveries, found that the interface between cultural underpinnings and modernity engenders identity-crisis, intricacies and persecution of black women in the contemporary (South) African society, with special focus to the Pedi/Northern Sotho tribal presumptions used as a case point.